Privacy-preserving ledger for blockchain and Internet of Things-enabled cyber-physical systems. (October 2022) - Singh, Rajani; Dwivedi, Ashutosh Dhar; Mukkamala, Raghava Rao; Alnumay, Waleed S.
Abstract: In recent years, decentralized applications such as Distributed Ledger Technologies and blockchain have evolved as suitable applications for secure sharing of information in a decentralized fashion using privacy preserving techniques like zero-knowledge protocols. However, the biggest issue with the traditional zero-knowledge protocols on a blockchain ledger is their slow performance on big data. This paper presents the advance zero-knowledge ledger by replacing their range-proof technique with the most efficient range-proof technique based on the improved inner product based zero-knowledge proofs. Moreover, this technique allows the aggregation of multiple range-proofs into a single range-proof, which makes the current zero-knowledge ledger system more efficient than the existing one. Graphical abstract: Highlights: Traditional zero-knowledge protocols are slow on blockchain ledger. This paper presents an advanced zero-knowledge ledger. This advanced zero-knowledge ledger system is more efficient.